Cultural Semiotics Literacy on Sonaf Tunbaba - Seran, Yanuarius; Nalenan, Joni Soleman (Universitas Nurul Jadid, 2024)
Sonaf Tunbaba is a house for the King while it becomes the centre for the continuity of all cultural activities including the customs of the Tunbaba community. The culture of the Tunbaba community is reflected through symbols or signs as differentiating meanings used in everyday life. As a differentiator of meaning, Sonaf Tunbaba is rich in cultural symbols that are meaningful and need to be known by all levels of society. The symbols on Sonaf Tunbaba are suspected to have a correlation with the symbol of the Unitary State of the Republic of Indonesia (NKRI). The main problem discussed in this study was how to express cultural semiotics in Sonaf Tunbaba. This study was carried out to determine and describe the meaning of cultural symbols contained in Sonaf Tunbaba. The researchers applied a descriptive qualitative method in this study. This study took cultural symbols on Sonaf Tunbaba as the object of this study. Sources of data were in form of primary and secondary data. The primary data were taken from Sonaf Tunbaba, while the secondary data were in form of interview’s result with informant. The data were analysed using semiotics theory. The result reflected that there were ten symbols found inside and outside the sonaf. Outside the sonaf, there were two symbols, namely an inscription monument and an offering altar. Inside the sonaf, there were eight symbols, namely terrace pillars with human face pictures, hangers, main pillars of the sonaf, a king’s pillar, an empress’ pillar, a storeyed altar, and a tribute.